2022
DOI: 10.1152/ajpheart.00291.2022
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake kinetics and chronotropic responses to exercise are impaired in survivors of severe COVID-19

Abstract: The post-acute phase of COVID-19 is often marked by several persistent symptoms and exertional intolerance, which compromise survivors' exercise capacity. This was a cross-sectional study aiming to investigate the impact of COVID-19 on oxygen uptake (VO2) kinetics and cardiopulmonary function in survivors of severe COVID-19 three to six months after intensive care unit (ICU) hospitalization. Thirty-five COVID-19 survivors previously admitted to ICU (5±1 months after hospital discharge) and 18 controls matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…Unfortunately, the study did not provide complete information about the medication of the patients. Similarly, in another study, the post-COVID patients had decreased chronotropic response, represented by decreased maximum heart rate, prolonged heart recovery time, and decreased chronotropic index [ 25 ]. In contrast with these results, we only found chronotropic incompetence in one patient.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unfortunately, the study did not provide complete information about the medication of the patients. Similarly, in another study, the post-COVID patients had decreased chronotropic response, represented by decreased maximum heart rate, prolonged heart recovery time, and decreased chronotropic index [ 25 ]. In contrast with these results, we only found chronotropic incompetence in one patient.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the extremely large numbers of studies dealing with COVID-19 and post-COVID syndrome, studies analyzing cardiorespiratory functions in post-COVID individuals are not as numerous. The vast majority of studies have confirmed that more severe COVID-19 infection leads to a more pronounced reduction in the exercise capacity [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Moreover, in all of the published studies, only a small number of patients were involved, and usually the involved individuals had survived more severe infection forms, or even individuals who were not discharged from the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Exertional intolerance is a common feature following COVID-19, especially in severe forms of the disease 3 4. Potential mechanisms for reduced exercise capacity include altered central (cardiac, pulmonary and autonomic) and peripheral (metabolic) parameters.…”
Section: Discussionmentioning
confidence: 99%
“…System was calibrated immediately before each test following manufacturer’s specifications. Outcome variables, including peak oxygen uptake (VO 2peak ), oxygen uptake at ventilatory threshold (VO 2VT ), oxygen uptake efficiency slope (OUES), respiratory exchange ratio (RER), pulmonary ventilation (V E ), ventilatory equivalent for carbon dioxide (V E /V CO2 ), O 2 pulse and chronotropic index were assessed as previously described 3 15 16. Heart rate recovery was assessed during the first (HRR 1min ), second (HRR 2min ) and fourth minute (HRR 4min ) of the recovery phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation